PUSAT KEBUDAYAAN DAYAK DI TABALONG - Adawiyah, Rabiatul; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Indonesia is an archipelagic country rich in cultural diversity, ethnicity and traditions. Culture is a habitual way of life and activities that grows and develops in an environment that is passed down from generation to generation. The move of the national capital from Jakarta to Kalimantan has become a new euphoria for all residents in Indonesia. This became the trigger for the entry of new cultures into Kalimantan. The Dayak tribe, which is an indigenous tribe in Kalimantan, is a tribe that is very rich in culture. However, if it is not addressed immediately the culture of the Dayak tribe can be eroded and threatened by incoming foreign cultures. The Dayak Cultural Center in Tabalong will elevate and increase the attractiveness of Dayak culture, as well as accommodate Dayak cultural activities and activities through the Dayak architectural DNA method as the first face to be seen at IKN with a neo-vernacular architectural concept approach as a form of maintaining Dayak culture.